Kepuasan Pasien terhadap Telehealth di Masa Pandemi Covid-19: Literature Review - Nurazizzi Setya Nadia; Diansanto Prayoga (Universitas Airlangga, 2023)
Background: The unfinished Covid-19 pandemic has caused various health services to be disrupted due to limiting face-to-face services. With this, health services must be transformed in order to maximize services with patients even though they cannot be served directly. as many as 71.8% of respondents chose not to go to a hospital or clinic and as many as 65.5% prefer to seek treatment digitally. Objectives: To find out the factors of patient satisfaction with telehealth services during the Covid-19 pandemic. Methods: his study uses a literature review method by applying the PRISMA flowchart. The databases used are Pubmed, Sage Publication, ScienceDirect, Proquest and Wiley Online. After getting the selection process, so that 12 journals were obtained that met the topics developed Discussion: Patients were satisfied with various telehealth services during this Covid-19 pandemic. Overall, it was found that young people were more accepting and satisfied with telehealth. The costs incurred by patients with the existence of telehealth are lower and the quality of telehealth services consists of patient trust in doctors, doctor-patient relationships, patient privacy is maintained. Conclusions: Factors of patient satisfaction with telehealth include age, cost and quality of service. Patients recognize that telehealth is very useful and facilitates them in terms of health consultations at a time of various limitations, thus enabling the development of telehealth in the future to be more rapid.